Особливостi електронної структури вуглецевих нановолокон та нанотрубок - Зауличний, Я.В.; Солонiн, Ю.М.; Звєзда, С.С.; Прилуцький, Е.В. (Видавничий дім "Академперіодика" НАН України, 2007)
The ultrasoft emission spectroscopy method is applied to investigate the energy distribution of
valence electrons in carbon nanoﬁbers and nanotubes. It has been revealed that the width of
emission bands in nanotubes is smaller than that in nanoﬁbers due to the energy redistribution
of valence electrons after the break of bonds when purifying nanotubes from catalysts. It has been
established that the difference between shapes of the emission bands of nanoﬁbers and nanotubes
is a consequence of the appearance of additional mixed π + σ-overlappings in nanotubes.